â€œ AleksandÃ«r Xhuvaniâ€ University - Troshani, Flutur (Richtmann Publishing, 2012)
My paper locates its point of departure inside the discourse of systemsâ€™ theory to examine how the postmodern interpretationof centeredness, both in poetry and poetics, has been remodeled. The point made in this paper is that in its most generic and metaphoricmanifestations, the idea of the center evinces deep ambivalence for postmodernism in general and postmodern poetry in particular.Hence, in the context of this multidisciplinary and sophisticated enterprise, the dynamics between stable and unstable, local and global,stability and fixity never resolves clearly. Throughout the most engaging body of poems by John Cage, John Ashbery, Robert Creeley,and John Berryman, which I will examine in my paper, the concept of centeredness sits uneasily against the cultural and aestheticpressures to produce that kind of poetry, which captures some of the most nuanced re-collections of the postmodern experience.